UNDERSTANDING ENSO DIVERSITY - Capotondi, Antonietta; Wittenberg, Andrew T.; Newmaman, Matthew; Di Lorenzo, Emamanuele; Yu, Jin-Yi; Braconnot, Pascacale; Cole, Julia; Dewitte, Boris; Giese, Benjamin; Guilyardi, Eric; Jin, Fei-Fei; Karnauskas, Kristopher; et al. (Bulletin of the American Meteorological Society, 2015)
El Niño–Southern Oscillation (ENSO) is a naturally occurring mode of tropical Pacific variability, with global impacts on society and natural ecosystems. While it has long been known that El Niño events display a diverse range of amplitudes, triggers, spatial patterns, and life cycles, the realization that ENSO’s impacts can be highly sensitive to this event-to-event diversity is driving a renewed interest in the subject. This paper surveys our current state of knowledge of ENSO diversity, identifies key gaps in understanding, and outlines some promising future research directions.